Secretome of hypoxia-preconditioned mesenchymal stem cells enhance the expression of HIF-1a and bFGF in a rotator cuff tear model - Meiky Fredianto; Herry Herman; Yoyos Dias Ismiarto; Agung Putra; Iffan Alif; Nur Dina Amalina; Muhammad Ariq Nazar (Medicinski glasnik, 2023)
Aim: To determine the effect of secretome hypoxia mesenchymal stem cells (SH-MSCs) on the relative gene expression of hypoxia inducible factor-1a (HIF-1a) and basic fibroblast growth factor (bFGF) in accelerating histomorphometric repair of tendon to bone interface healing in rats acute rotator cuff tear (RCT) model. Methods: This is experimental research with posttest control group design. Thirty-male Wistar rats were divided into five treatment groups: healthy group and rotator cuff reconstruction group included four groups: SH-MSCs W2 (the treatment group was given a SH-MSCs 0.5 mL and terminated at weeks 2), NaCl W2 (the control vehicle group was assigned NaCl 0.5 mL and terminated at weeks 2), SH-MSCs W8 (the treatment group was given a SHMSCs 0.5 mL and terminated at weeks 8), and NaCl W8 (the control vehicle group was given NaCl 0.5 mL and terminated at weeks 8). All the rats were terminated on day termination and HIF-1a and bFGF gene expression were analysed using qRT-PCR. Results: SH-MSCs significantly increased the HIF-1a and bFGF gene expression than the NaCl group even in week 2 and week 8. The highest increased gene expression of HIF-1a and bFGF was on week 8. Conclusion: SH-MSCs are important in the healing repair process of the tendon-to-bone interface in acute RCT model rats through increasing gene expression of HIF-1? and bFGF.
Keywords: bFGF; HIF-1α; MSCs; rotator cuff tear